You are on page 1of 13

BY :

ALTA DWI DINIENGGA B. (04)


ARWIN DAHRIL N. (06)
AYU WIJI A. (07)
EKA PUTRI Y. (11)
RIZKY BADILLAH N. (23)
YOGA ALGHAZALI A. (29)





Factors are the numbers you multiply together to get
another number:

Example: 3 and 4 are factors of 12, because 3x4=12.

Also 2x6=12 so 2 and 6 are also factors of 12, and
1x12=12 so 1 and 12 are factors of 12 as well.

So ALL the possible factors of 12 are 1,2,3,4,6 and 12.
Example :
2x
2
+ 8x + 6 = 0 From the result, we know that
(2x + 6 ) ( x + 1 ) = 0 although the way is different, but
2x + 6 = 0, x + 1 = 0 the result is same . . . . . . .
2x = - 6 x = -1 x = -3 , x = -1
x = -3
x = -3 , x = -1
Or
(2 x + 6 ) (2 x + 2 ) = 0
( x + 3 ) ( 2x + 2 ) = 0
x + 3 = 0 2x + 2 = 0
x = - 3 2x = -2
x = -1
Example
Simplify quadratic factor in the bellow
X
2
3x + 2 = 0

Answer :
Quadratic factor
x
2
3x + 2 = 0
(x - 2)(x 1)=0
End up ,x 2 = 0 ; x - 1 = 0
x = 2 x = 1
Solving Quadratic
Equations
Unfortunately, most quadratics don't come
neatly squared like this. For your average
everyday quadratic, you first have to use the
technique of "completing the square" to
rearrange the quadratic into the neat
"(squared part) equals (a number)" format
demonstrated above.

Example :
Find the x-intercepts of y = 4x
2
2x 5.

This is the original problem. 4x
2
2x 5 = 0
Move the loose number over to the other side. 4x
2
2x = 5
Divide through by whatever is multiplied on
the squared term.
Take half of the coefficient (don't forget the
sign!) of the x-term, and square it. Add this
square to both sides of the equation.
Convert the left-hand side to squared form,
and simplify the right-hand side. (This is
where you use that sign that you kept track of
earlier. You plug it into the middle of the
parenthetical part.)
Square-root both sides, remembering the ""
on the right-hand side. Simplify as necessary.
Solve for "x =".
Remember that the "" means that you have
two values for x.
Solve x
2
+ 6x 7 = 0 by completing the square.

Solution :
This is the original equation.
x
2
+ 6x 7 = 0
Move the loose number over to the other side.
x
2
+ 6x = 7
Convert the left-hand side to squared form. Simplify the right-hand
side.
(x + 3)
2
= 16
Square-root both sides. Remember to do "" on the right-hand side.
x + 3 = 4
Solve for "x =". Remember that the "" gives you two solutions.
Simplify as necessary.
x = 3 4
x
1
= 3 + 4 x
2
= -3- 4
= 1 = -7

1. Consider the general quadratic equation


with a0

2. Start by dividing coefficient of
x
2
= a
x = b
constant = c
ax
2
+ bx + c = 0
3. Input formula



4. Remark. The plus-minus sign states
that you have two numbers.
x
1
=

x
2
=
Use the Quadratic Formula to solve


Solution :
a = 2, b = -3, c =


x
1
=
3 +5
x
2
=
3 -5


4 4